Exploring how playing football with different age groups affects tactical behaviour and physical performance - Figueira, Bruno; Gonçalves, Bruno; Masiulis, Nerijus; Sampaio, Jaime (Biology of Sport, 2018)
The study aimed to compare footballers’ performances when playing with teammates and opponents from the same age group with performances when playing with teammates and opponents of different age groups. Three football matches were played: i) under-15 (U15) players played with each other; ii) under-17 (U17) players played with each other; and iii) players under the age of 15 and 17 played with each other in two equivalent mixed age teams. The players’ physical performance was measured using the distances covered at different speed categories and tactical behaviour was assessed using several positioning-derived variables. The results showed that, when playing in the mixed age condition, the U15 players increased the distance covered in sprinting intensity (18.1%; ±21.1%) and the U17 players increased the distance covered in jogging zones (6.8%; ±6.5%). The intra-team movement synchronization in longitudinal and lateral displacements was higher when U15 players confronted peers of the same age, in the first half (-13.4%; ±2.0%, -20.3%; ±5.7% respectively), and when U17 players confronting the mixed group, in both halves (-16.9%; ±2.5%, 9.8%; ±4.0% and 7.9%; ±5.7%, 10.6% ±4.4%, respectively). The differences between age groups and the mixed condition may be connected with the level of players’ tactical expertise and adaptive positioning according to the dynamic environmental information. In general, these results suggest that mixing the age groups may be useful to promote a wider range of training session stimuli in these young football players.